2005
DOI: 10.3748/wjg.v11.i12.1747
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and therapeutic effects of NF-kappaB inhibitor curcumin in rats colitis induced by trinitrobenzene sulfonic acid

Abstract: This study shows that NF-kappaB inhibitor curcumin could prevent and improve experimental colitis in murine model with inflammatory bowel disease (IBD). The findings suggest that NF-kappaB inhibitor curcumin could be a potential target for the patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
99
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 29 publications
9
99
1
Order By: Relevance
“…The molecular mechanism involved in the suppressive effects of Curcumin on NFκ-B could be due to the inhibition of NFκ-B by acting as antioxidants, since NFκ-B is a redox-sensitive transcription factor and activated by oxidative stress in the inflamed intestinal mucosa via blocking the phosphorylation and degradation of IkB protein, as previously reported in vitr o and in vivo [7,19] .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The molecular mechanism involved in the suppressive effects of Curcumin on NFκ-B could be due to the inhibition of NFκ-B by acting as antioxidants, since NFκ-B is a redox-sensitive transcription factor and activated by oxidative stress in the inflamed intestinal mucosa via blocking the phosphorylation and degradation of IkB protein, as previously reported in vitr o and in vivo [7,19] .…”
Section: Discussionmentioning
confidence: 86%
“…The results obtained in this study confirm the intestinal anti-inflammatory effect previously demonstrated for Curcumin [9,17] . Earlier studies provided evidence of significantly elevated activation of NFκ-B in ulcerative colitis and Crohn's disease [18,19] . Several therapeutic agents with NFκ-B inhibitory activity, such as sulfasalazine, mesalamine, and corticosteroids have been used for the treatment of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The prophylactic Curcumin regimen (Group II) had a lower statistically significant muscle TAC value than the therapeutic regimen (Group III). Previous studies on other models of inflammation (murine colitis) reported the preventive and therapeutic effects of Curcumin (Jiang et al, 2006;Jian et al, 2005;Arafa et al, 2009). Research performed on human subjects concluded that short-term supplementation with bioavailable Curcumin significantly improves the inflammatory and oxidative status of patients, suggesting the benefits of prophylactic administration, with no toxicity risk (Menon and Sudheer, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In numerous experimental murine models of colitis, there is evidence that curcumin has potential therapeutic and preventive benefits that may be applicable in the treatment of IBD 8,14,19 . Previously, using the human intestinal cell line (HCT116, HT-29 and CaCO 2 ), it was shown that curcumin pretreatment inhibited and modulated gene expression of IL-8 in response to inflammatory cytokine exposure 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…In inflammatory bowel disease (IBD), curcumin is proposed as an attractive alternative therapy to the conventional medicines 5,6 . Curcumin is considered to be safe and inexpensive 7 and emerging evidence from pre-clinical studies indicates the potential benefits of curcumin supplementation in IBD [8][9][10][11] . Clinical trials of curcumin have included a pilot study involving 5 patients with chronic ulcerative proctitis and 5 patients with Crohn's disease (CD) 12 .…”
Section: Introductionmentioning
confidence: 99%